Lords & Lemurs: Mad Scientists, Kings with Spears, and the Survival of Diversity in Madagascar (Book). - Boynton, Andy (Booklist, 2004)
Reviews the book “Lords & Lemurs: Mad Scientists, Kings with Spears, and the Survival of Diversity in Madagascar,” by Alison Jolly.